IMPLEMENTASI PROGRAM BUBACO: PENGUATAN LITERASI HURUF DAN KARAKTER PERCAYA DIRI DI KELAS I - Yuli Kurniasih; Wildan Nurul Fajar (STKIP Subang, 2026)
This study aims to describe the design process, implementation, and impact of the BUBACO Program (Buka-Baca-Cocok) as a character education innovation in Grade I of SD Negeri Sidareja 06. The study was grounded in a dual gap observed in the classroom: the majority of students had not yet mastered basic alphabet recognition, while nearly all participants showed marked reluctance to read aloud in front of peers2014a condition reflecting an intertwined deficit in both foundational literacy and self-confidence. A qualitative approach with a single case study design was employed. Data were collected through participant observation, document analysis of student worksheets and character observation sheets, anecdotal records, and field notes, then analyzed using the interactive model of Miles, Huberman, and Saldana. The BUBACO Program integrates a four-step interactive flashcard method2014Buka (Open), Baca (Read), Cocok (Match), and Tempel (Attach)2014that simultaneously cultivates literacy and character. Findings reveal consistent and progressive improvements across both domains: letter recognition developed from a low baseline toward near-mastery, while self-confidence transformed dramatically, with most participants eventually volunteering to present independently before their peers. Effectiveness is explained through Bandura2019s social learning theory, Lickona2019s character framework, Dweck2019s growth mindset, and CASEL2019s social-emotional competencies. The novelty lies in three dimensions: conceptually integrating literacy and character within one media design; methodologically documenting the full innovation cycle through a single case study; and contextually demonstrating that meaningful innovation can emerge from technological constraints. The BUBACO Program is a simple, contextual, and replicable model for elementary teachers.